Edukasi Cara Menyikat Gigi Dengan Benar dalam Pencegahan Karies Gigi pada Siswa-Siswi di SDN 03 Kabawetan - Ridho Anfal Pradillah; Undal Rhomadhon; Della Puspita Sari; A’izzah Al-hasanah; Puput Adilla Putri Alam; Emi Febriani (Universitas Dehasen Bengkulu, 2026)
Dental caries is one of the health problems that often occur in elementary school children, which can have an impact on quality of life and learning achievement. This study aims to determine the effectiveness of dental health counseling in improving children's knowledge, attitudes, and behaviors related to the prevention of dental caries. The research was conducted at SD Negeri 03 Kabawetan, Sumber Sari Village, Kabawetan District, Kepahiang Regency, in 2025. Counseling was carried out using interactive methods, including lectures, demonstrations of correct brushing, and the use of educational media in the form of videos and posters. Data was collected through questionnaires to measure knowledge, attitudes, and behaviors before and after counseling. The results showed a significant increase in children's knowledge score (p < 0.05), attitude (p < 0.05), and behavior (p < 0.05) related to the prevention of dental caries. In addition, students showed high enthusiasm for counseling methods that involved hands-on practice and visual media. The conclusion of this study is that interactive dental health counseling is effective in increasing understanding and forming healthy living habits in elementary school age children.